Sosyal Güvenlik Kurumunca yapılan fazla veya yersiz ödemelerin geri alınması - Pekşen, Miraç Şamil (My University, 2025)
Yersiz ödeme, Sosyal Güvenlik Kurumunun yapmaması gereken ya da yapması gerekenden daha fazla miktarda yaptığı ödemedir. Hukukumuzda yersiz ödemelerin geri alınmasına ilişkin temel düzenlemeler 5510 sayılı Sosyal Sigortalar ve Genel Sağlık Sigortası Kanunun 96. maddesi ve bu maddeye dayanılarak hazırlanan Fazla veya Yersiz Ödemelerin Tahsiline İlişkin Usul ve Esaslar Hakkında Yönetmelik hükümleridir. Sosyal Güvenlik Kurumunun aktüeryal dengesini olumsuz yönde etkileyen yersiz ödemelerin geri alınması gerekmektedir. Ancak hukukumuzdaki yersiz ödemelerin geri alınması sistemi adaletsiz sonuçlar doğurmakta, kendisine yersiz ödeme yapılan iyiniyetli kişileri mağdur etmektedir. Zira yersiz ödemelerin geri alınmasına ilişkin mevzuat hükümleri düzenlenirken ilgililerin iyiniyeti dikkate alınmamış, Sosyal Güvenlik Kurumunun hatalı işlemlerinden ilgililer sorumlu tutulmuş ve yersiz ödemelerin tespiti süre açısından sınırlandırılmamıştır. Çalışmamızda yersiz ödemelerin geri alınmasına ilişkin hukukumuzdaki sistem yer yer Alman Hukuku ile karşılaştırılarak incelenmiştir. Yapılan inceleme neticesinde, anılan sistemin temelini oluşturan 5510 sayılı Kanunun 96. maddesinin çeşitli nedenlere Anayasaya aykırı olduğu tespit edilmiştir. Ayrıca, söz konusu düzenleme bazı temel hukuk ilkelerine de aykırıdır. Yersiz ödemelerin geri alınması sisteminin olumsuz sonuçları nedeniyle çeşitli istisna ve af hükümleri düzenlenmiştir. Kanaatimizce yersiz ödemelerin geri alınması sistemi, istisnalara ve af hükümlerine gerek kalmayacak şekilde yeniden düzenlenmelidir. Bu yapılırken sebepsiz zenginleşme hükümlerinden, idari işlemin geri alınmasına ilişkin idare hukuku prensiplerinden ve Alman Hukukundaki düzenlemelerden faydalanılmalıdır.

Payments made by the Social Security Institution that it should not have made or that exceed the amount that should have been paid are referred to as improper payments. The main regulations regarding the recovery of improper payments in Turkish Law are Article 96 of the Social Insurance and General Health Insurance Law No. 5510 and the Regulation on the Procedures and Principles Regarding the Collection of Over or Improper Payments prepared on the basis of this article. Improper payments, which negatively affect the actuarial balance of the Social Security Institution, must be recovered. However, the system for recovering improper payments in Turkish Law leads to unfair outcomes and victimizes the bonafide persons who have received improper payments. Because the legislative provisions regarding the recovery of improper payments were drafted the good faith of the concerned parties was not taken into account, these parties were held responsible for the Social Security Institution's erroneous transactions, and the detection of improper payments was not limited in terms of time. In our study, the system in Turkish Law regarding the recovery of improper payments is analyzed by comparing it with German Law. As a result of this examination, it has been determined that Article 96 of Law No. 5510, which forms the basis of the system, is unconstitutional for various reasons. Furthermore, this said regulation is contrary to some fundamental principles of law. Due to the negative consequences of the system of recovery of improper payments, various exceptions and amnesty regulations have been regulated. In our opinion, the system of recovery of improper payments should be reorganized in such a way that there is no need for exceptions and amnesty regulations. While doing so, the provisions on unjust enrichment, the principles of administrative law regarding the withdrawal of administrative acts, and the regulations in German Law should be taken as a basis.
Keywords: İş hukuku Social security law; Labour law; Social security; Sosyal güvenlik; Sosyal güvenlik hukuku; Turkey; Türkiye